2022
DOI: 10.1038/s41378-022-00415-w
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing metabolic activity and differentiation potential in adipose mesenchymal stem cells via high-resolution surface-acoustic-wave contactless patterning

Abstract: Acoustofluidics has shown great potential for label-free bioparticle patterning with excellent biocompatibility. Acoustofluidic patterning enables the induction of cell–cell interactions, which play fundamental roles in organogenesis and tissue development. One of the current challenges in tissue engineering is not only the control of the spatial arrangement of cells but also the preservation of cell patterns over time. In this work, we developed a standing surface acoustic wave-based platform and demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…However, the addition of GO to GelMA enhances this response, with GelMA-GO (striped pink) showing the most significant increase under both passive and stimulation regimes indicating a consistent enhancement independent of stimulation. 78 By day 3, cells across all hydrogels show enhanced metabolic activity under stimulation, suggesting either enhanced cell proliferation or increased metabolic functioning. 79 On day 7, the overall increase in metabolic activity under stimulation remains consistent, indicating a potential stimulation effectiveness over prolonged periods.…”
Section: Acsmentioning
confidence: 94%
“…However, the addition of GO to GelMA enhances this response, with GelMA-GO (striped pink) showing the most significant increase under both passive and stimulation regimes indicating a consistent enhancement independent of stimulation. 78 By day 3, cells across all hydrogels show enhanced metabolic activity under stimulation, suggesting either enhanced cell proliferation or increased metabolic functioning. 79 On day 7, the overall increase in metabolic activity under stimulation remains consistent, indicating a potential stimulation effectiveness over prolonged periods.…”
Section: Acsmentioning
confidence: 94%
“…Martinez Villegas et al 142 demonstrated the enhancement of the osteogenic differentiation and proliferation of adipose-derived stem cells embedded into a photocurable hydrogel via acoustic patterning using a frequency of 13.11 MHz (SSAW). Furthermore, Devendran et al 143 scrutinized the phenotypes of four distinct human and mouse cell lines after exposure to 48.5 MHz (SAW).…”
Section: Acoustofluidics As a Functional Force For Investigating Phen...mentioning
confidence: 99%
“…In fact, there is increasing evidence that preparing cells as 3D tissue-like structures with a certain spatial structure enhances their secretory activity. [62] This may be related to the formation of more cell-cell and cell-ECM interactions, [74,75] as well as cell responses to changes in spatial curvature. [76] The distinct advantage of cell sheets over spheroids in the field of tissue engineering is that cell sheets can be relatively easily combined into macrostructures, so that scaffold-free multicellular platforms with multiple repair functions can be prepared.…”
Section: Cell Sheetsmentioning
confidence: 99%
“…[79] Because the relationship between cells is much closer to that of tissues, the cell behavior and growth reflected by the cells in cell sheets can better reflect the actual physiological situation. To reproduce the distribution of cells in complex tissues as much as possible, many researchers have used micropattern, [84,85] microcontact printing, [86] magnetic or acoustic control, [75,87] and other methods to regulate cell distribution and explore the crosstalk between different cells in complex models. However, the structural complexity obtained by these methods is still not enough.…”
Section: Magnetic Controlmentioning
confidence: 99%